Giardia sp. and Cryptosporidium sp. in Iberian Wolf - PEREIRA, A.L.; MATEUS, T. L.; LLANEZ, L.; DUARTE, S. D. (Journal of the Hellenic Veterinary Medical Society, 2019)
A subsample consisting of fifty fecal samples from wild Iberian Wolf (Canis lupus signatus), from the northwest of Spain were collected in the field. The samples were analyzed for cysts of Giardia sp. and oocysts of Cryptosporidium sp. using a direct immunofluorescence antibody test (IFA). Giardia sp. and Cryptosporidium sp. were found in 20.0 % of the samples examined. Simple infections were more frequent (90.0 %) with seven (14.0 %) positive for Giardia sp. and two (4.0 %) positive for Cryptosporidium sp. To the authors’ knowledge, this is the first report of occurrence of Cryptosporidium sp. in Iberian Wolf.